Keloris Puri Kelorina Participatory Communication Model to Empower Ngawenomboh Village - Fadeli, Mohammed; Setyarahajoe, Ratna; Fitriawardhani, Tira (Faculty of Law, Universitas Pekalongan, 2024)
This research focuses on participatory communication model in community empowerment in Ngawenomboh Village, Central Java. Keloris as the program implementer is involved in cultivation, production process and cooperation with Moringa production and distribution partners for healthy processed products. The research method uses a qualitative descriptive approach through interviews and observations. Through dialogue, polyphony, and carnival keloris managed to build relationships based on mutual respect and cooperation towards achieving common goals in empowerment. The intense and open participatory communication can result in strong collaboration, increasing the success of community empowerment efforts. Therefore it needs to be strengthened to achieve better changes.